KENDALA IMPLEMENTASI KURIKULUM 2013 PADA PEMBELAJARAN IPS KELAS VIII SMP TAHUN AJARAN 2018/2019 DI KECAMATAN NANGGALO KOTA PADANG - Santi kartika sari; Khairani Khairani (JURUSAN GEOGRAFI FIS UNP, 2019)
Abstract This study aims to determine the planning, implementation, assessment / evaluation, and constraints of 2013 Curriculum Implementation. This type of research is the Mixed-Method method. The population in this study amounted to 13 social studies teachers. Sampling using purposive sampling technique. The sample taken was 7th grade social studies teacher in VIII. The technique of collecting data through interviews, questionnaires, and documentation. Data analysis techniques used triangulation techniques. The results of this study indicate there are obstacles to the readiness of teachers in the suitability of the use of time allocation when learning with lesson plans, the ability of teachers to implement scientific learning steps, and the ability of teachers to accommodate integrated learning.